Respostas

2014-07-19T17:56:53-03:00
5 (2x - 4) + 7 (- 1 + x^9) = 125 + 18
10x - 20 - 7 + 7x^9 = 125 +18
10x - 20 - 7 + 7x^9 - 125 - 18
7x^9+ 10x - 20 - 7 - 125 - 18
7x^9 + 10x - 27 - 143
7x^9 + 10x - 170 = 0
Δ = 10² - 4.7.(- 170)
Δ = 100 + 4 760
Δ = 4 860

x = - 10 + - √ 4 860 / 14
x = - 10 + - √ 2² . 3² . 3² . 3 . 5 / 14
x = - 10 + - 18 √ 15 / 14

x ' = - 10 + 18 √ 15 / 14 = 8 √ 15 / 14 

x '' = - 10 - 18 √ 15 / 14 = - 28 √ 15 / 14 = - 2 √ 15 


OU depende se for x^9 ou 9x

5 (2x - 4) + 7 (- 1 + 9x) = 125 + 18 
10x - 20 - 7 + 63x - 125 - 18 = 0
10x + 63x - 20 - 7 - 125 - 18 = 0
73x - 27 - 143 = 0
73x - 170 = 0
73x = 170
x = 170 / 73